Faktor-faktor yang Mempengaruhi Tingkat Resiko Persalinan Ibu Menggunakan Analisis Regresi Probit (Studi Kasus RST Reksodiwiryo Padang) - Zilla Zalila; Nonong Amalita (Universitas Muhammadiyah Semarang, 2018)
Every mother who will do childbirth generally wants a normal childbirth. But in reality, many mothers give birth abnormally. Based on the 2015 Indonesian Demographic Health Survey (IDHS), the Maternal Mortality Rate (MMR) in Indonesia is still quite high that reaching 305 per 100,000 people. The purpose of this study was to determine the form of probit regression models of the factors that influence the risk level of maternal childbirth, describing what factors that influence the level of risk of maternal childbirth, and the opportunities of factors that influence the risk level of maternal childbirth in RST Reksodiwiryo Padang.Based on the results of the study, the best probit regression model that describes the factors that influencethe risk level of maternal childbirth in RST Reksodiwiryo Padang in July, August, and September Tri-Wulan are:(Pi) = 0,808 + 1,295 X3 + 1,334 X4 + 0,878 X7 – 1,819 X8 Keyword:Probit regression analysis, the level of risk of maternal childbirth